2011
DOI: 10.1016/j.bpg.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrogenic strategies and the regression of fibrosis

Abstract: Liver fibrosis is an outcome of many chronic diseases, and often results in cirrhosis, liver failure, and portal hypertension. Liver transplantation is the only treatment available for patients with advanced stage of fibrosis. Therefore, alternative methods are required to develop new strategies for anti-fibrotic therapy. Available treatments are designed to substitute for liver transplantation or bridge the patients, they include inhibitors of fibrogenic cytokines such as TGF-β1 and EGF, inhibitors of rennin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 115 publications
3
112
0
Order By: Relevance
“…Pivotal studies have demonstrated that liver fibrosis is not always an irreversible condition provided that underlying etiological agents are removed, as has been the case with secondary biliary fibrosis, Hepatitis C, Hepatitis B, steatohepatitis, and autoimmune hepatitis [192].…”
Section: Ppars Stimulation Strategies Therapymentioning
confidence: 99%
“…Pivotal studies have demonstrated that liver fibrosis is not always an irreversible condition provided that underlying etiological agents are removed, as has been the case with secondary biliary fibrosis, Hepatitis C, Hepatitis B, steatohepatitis, and autoimmune hepatitis [192].…”
Section: Ppars Stimulation Strategies Therapymentioning
confidence: 99%
“…However, the in vivo inhibition of endogenous TIMP-1 expression remained unclear. Recombinant adenovirus is highly efficient for both in vitro and in vivo transfection, for a wide range of infected cells, it can infect quiescent and mitotic cells, and it does not integrate into the host cell genome; thus, the adenovirus has wide application potential in gene engineering and gene therapy (Hammann et al, 2007;Kisseleva and Brennern, 2011). In this experiment, we chose TIMP-1shRNA as the target gene fragment and recombinant adenovirus plasmid Adeno-X TM as gene therapy vector and successfully inserted the TIMP-1shRNA gene fragment into the recombinant adenovirus vector.…”
Section: Discussionmentioning
confidence: 99%
“…Activated myofibroblasts are the primary target for antifibrotic therapy, because a reduction in activated myofibroblasts may lead to a reversal of fibrosis (Brenner 2009;Kisseleva and Brenner 2011). Inactivation of myofibroblasts is also expected to cease fibrosis.…”
Section: Potential Antifibrotic Therapiesmentioning
confidence: 99%